(untitled) - Fransman, Martin (Oxford, 1995)
This work draws on and extends the theoretical framework developed by such authors as Richard Nelson, Sidney Winter, David Teece, Alfred Chandler, Nathan Rosenberg, and Christopher Freeman, through an empirical analysis of the evolution of the Japanese information and communications (IC) industry. Particular attention is paid to the development of a theory of the firm which is consistent with this empirical objective
Keywords: Computer industry,Công nghiệp máy tính,Công nghiệp thiết bị viễn thông,Telecommunication equipment industry; Japan,Nhật Bản,Nhật Bản,Japan